2012
DOI: 10.1038/nature11436
|View full text |Cite
|
Sign up to set email alerts
|

Severe stress switches CRF action in the nucleus accumbens from appetitive to aversive

Abstract: Stressors motivate an array of adaptive responses ranging from “fight or flight” to an internal urgency signal facilitating long-term goals1. However, traumatic or chronic uncontrollable stress promotes the onset of Major Depressive Disorder where acute stressors lose their motivational properties and are perceived as insurmountable impediments2. Consequently, stress-induced depression is a debilitating human condition characterized by an affective shift from engagement of the environment to withdrawal3. An em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
272
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 281 publications
(295 citation statements)
references
References 35 publications
17
272
3
3
Order By: Relevance
“…Excitingly, recent rodent research has provided a potential pharmacological mechanism by which this modulation may occur (17). In particular, it has been shown that stress switches the role of corticotropin-releasing hormone (CRH) in the striatum from driving corticotropin-releasing factor receptor (CRFR) 1 and CRFR2…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Excitingly, recent rodent research has provided a potential pharmacological mechanism by which this modulation may occur (17). In particular, it has been shown that stress switches the role of corticotropin-releasing hormone (CRH) in the striatum from driving corticotropin-releasing factor receptor (CRFR) 1 and CRFR2…”
Section: Discussionmentioning
confidence: 99%
“…SF, safe-fear; SH, safe-happy; TF, threat-fear; TH, threat-happy. receptor-linked appetitive responding to aversive responding, driving "a diametric change in the emotional response to acute stressors" (17). This is particularly relevant because we know that the anxiogenic effects of the translational threat-of-shock paradigm used here are CRH dependent (18).…”
Section: Fig 1 (A)mentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, the effects of GCs on social behavior may depend on the social and environmental context (Orchinik, 1998) as well stressor severity (Lemos et al., 2012). GCs are regarded mainly as permissive or facilitating hormones behind many behaviors, such as self‐grooming or feeding (Katz & Roth, 1979; Packard et al., 2016; Rowland & Antelman, 1976).…”
Section: The Potential Role Of the Stress Axis In Mediating Social Bementioning
confidence: 99%
“…For example, GCs may promote as well as inhibit aggression toward conspecifics depending on social rank, personality and the duration of the stressor (Grace & Anderson, 2014; Summers et al., 2005). Furthermore, while acute HPA‐axis activity may trigger dopamine production, severe stress is known to abolish this rewarding effect and lead to social withdrawal (Lemos et al., 2012). …”
Section: The Potential Role Of the Stress Axis In Mediating Social Bementioning
confidence: 99%